Peningkatan Kemandirian Dan Hasil Belajar Menggunakan Model Reciprocal Teaching Melalui Pendekatan Team Assisted Individualization (TAI) - Suharmanto (CV. Multi Kreasi Media, 2022)
This research aims to realize an effective learning approach in supporting students in the learning process so that students are able to develop their abilities and competencies in the field they are currently practicing. This study uses a method based on the acquisition of research data by way of observation, tests to determine ratings, and documentation and analysis using a qualitative descriptive approach. In this study it was concluded that the application of the TAI learning model can help in improving student learning outcomes in the subjects of chassis maintenance and light vehicle power transfer. It can be seen that the value of student learning outcomes after taking action or applying the TAI learning model has increased the class average score with a 100% pass rate.